2013
DOI: 10.1002/asna.201211973
|View full text |Cite
|
Sign up to set email alerts
|

A quest for activity cycles in low‐mass stars

Abstract: Long-term photometric measurements in a sample of ultrashort-period (P ≈ 0.5 days or less) single and binary stars of different interior structures are analysed. A loose correlation exists between the rotational rate and cycle lengths of active stars, regardless of their evolutionary state and the corresponding physical parameters. The shortest cycles are expected for the fastest rotators of the order of 1-2 years, which is reported in this paper.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…005 amplitude) corresponding to P = 0.445518 days in the Fourier spectrum is seen. If we accept this as a signal that also stems from the rotation, this would yield a differential rotation shear of |α| = |∆P/P| 0.0004, which is very close to a rigid-body rotation, in agreement with the findings of Vida et al (2013), of Morin et al (2008a) (α = 0.0004), and of Donati et al (2006) (α = 0.0014). On GJ 1243, another M4 star with a fast rotation of 0.59 days, Davenport et al (2015) found a similar differential rotation (|α| = 0.0011) to our estimate on V374 Peg.…”
Section: Fourier Analysissupporting
confidence: 76%
“…005 amplitude) corresponding to P = 0.445518 days in the Fourier spectrum is seen. If we accept this as a signal that also stems from the rotation, this would yield a differential rotation shear of |α| = |∆P/P| 0.0004, which is very close to a rigid-body rotation, in agreement with the findings of Vida et al (2013), of Morin et al (2008a) (α = 0.0004), and of Donati et al (2006) (α = 0.0014). On GJ 1243, another M4 star with a fast rotation of 0.59 days, Davenport et al (2015) found a similar differential rotation (|α| = 0.0011) to our estimate on V374 Peg.…”
Section: Fourier Analysissupporting
confidence: 76%
“…For this, we carefully selected 47 single, inactive M dwarfs with previous published P cycle and P rot (Savanov 2012;Robertson et al 2013;Suárez Mascareño et al 2016, 2018Wargelin et al 2017;Küker et al 2019) and the stars of our sample for which we have found P cycle and P rot (see Table 2). In our sample of field M dwarfs we did not include fast-rotating, probably very young M dwarfs tabulated by Vida et al (2013Vida et al ( , 2014 and Distefano et al (2016Distefano et al ( , 2017. Figure 8 shows the plot P cycle /P rot vs. 1/P rot in log-log scale.…”
Section: Long-period Cyclesmentioning
confidence: 99%
“…8, we plot the cycle period (in years) vs. the stellar rotation period (in days) for the sample stars. We use the stellar sample discussed in detail by Brandenburg et al (1998) and Böhm-Vitense (2007) (blue and green triangles), the stars with confirmed X-ray cycles discussed in the introduction section (magenta circles) and individual fast rotators with activity cycles as discussed by Bernhard & Frank (2006), Taš (2011), andVida et al (2013) (red circles); the data point for AB Dor A is also shown, using its 0.52 day rotation period and 17 year activity-cycle period. Brandenburg et al (1998) showed that active and inactive stars follow different branches in a P cyc − P rot -diagram.…”
Section: Comparison Of Ab Dor A's Activity Cycle With That Of Other Smentioning
confidence: 99%